Betamethasone use and risk factors for pulmonary edema during the perinatal period: a single-center retrospective cohort study in Japan - Nishikawa, Takashi; Fukuhara, Ken (BMC Pregnancy and Childbirth, 2022)
Background A few studies have reported that maternal administration of antenatal corticosteroids increased the risk of pulmonary edema (PE). However, despite the increasing usage rate of betamethasone as antenatal corticosteroid, maternal administration of betamethasone as a risk factor for PE has not been well studied. This study aimed to evaluate how maternal backgrounds and complications, tocolytic agents, and betamethasone affect the incidence of PE during the perinatal period and determine the risk factor for PE. Methods This was a single-center retrospective cohort study in Kurashiki, Japan. The study subjects were patients who had been admitted to our hospital for perinatal management including pregnancy, delivery and puerperium between 2017 and 2020. The primary outcome measure was defined as the incidence of PE during hospitalization. First, in all study subjects, Cox proportional hazards model was used to determine the risk factor for PE during the perinatal period. Next, using propensity score matching, we divided the patients into the betamethasone and betamethasone-free groups and examined the association between betamethasone use and the incidence of PE with Cox proportional hazards model. Results During the study period, 4919 cases were hospitalized, and there were 16 PE cases (0.3%). In all analyzed subjects, the occurrence of PE was significantly associated with preeclampsia (hazard ratio 16.8, 95% confidence intervals (CI) 5.39–52.7, P < 0.001) and the combined use of the tocolytic agents such as ritodrine hydrochloride and magnesium sulfate, and betamethasone (hazard ratio 11.3, 95% CI 2.66–48.1, P = 0.001). In contrast, after propensity score matching, no statistically significant difference was found between the betamethasone and betamethasone-free groups in the incidence of PE (hazard ratio 3.19, 95% CI 0.67–15.3, P = 0.145). Conclusions A combined use of tocolytic agents and antenatal corticosteroids such as betamethasone may be an independent risk factor for PE during the perinatal period. On the other hand, betamethasone use alone may not be associated with the incidence of PE. When tocolytic agents and betamethasone are administrated to pregnant women, it is important to pay attention to the appearance of maternal respiratory symptoms.